2015
DOI: 10.1139/cjm-2015-0107
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and antimicrobial susceptibility of clinical and environmental strains of Aeromonas spp. from northeastern Brazil

Abstract: The aims of the present study were to isolate and identify clinical and environmental strains of Aeromonas spp. by means of biochemical tests and the automated method VITEK 2 and to investigate the presence of the virulence genes cytotoxic enterotoxin (act), hemolysin (asa-1), and type III secretion system (ascV), and also the in vitro antimicrobial susceptibility of the strains. From the clinical isolates, 19 Aeromonas hydrophila, 3 Aeromonas veronii bv. sobria, and 1 Aeromonas caviae were identified, while f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…However, it may be explained by different expression level of the genes or interaction with other virulence factor not included in this study. Inconsistent with previous study [7], no particular pattern of virulence genes was observed in this study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, it may be explained by different expression level of the genes or interaction with other virulence factor not included in this study. Inconsistent with previous study [7], no particular pattern of virulence genes was observed in this study.…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence and dangerousness of Aeromonas infections seems to be underestimated, as they vary among different geographic regions and type of infections [7], but there are not enough fundamental reports in many countries. Wenzhou, a coastal city located in southeast China with subtropical climate, is prone to Aeromonas infection due to the humid weather.…”
mentioning
confidence: 99%
“…Castelo-Branco et al [28] observed that Aeromonads of clinical origin had fewer virulence genes than those isolated from other sources. In our study, it was possible to observe variations in the relationship between virulence genes and source, thus indicating that the distribution of virulence genes among Aeromonas is not uniform.…”
Section: Discussionmentioning
confidence: 99%
“…dhakensis and A. aquariorum) resistant to cefoxitin were also described by Esteve et al (2012) and Figueras et al (2009), agreeing with the findings of the present study to the South American strain. The resistance to meropenem, on the other hand, is noteworthy, as aeromonads are usually sensitive to carbapenems (Yucel & Erdogan 2010;Liu et al 2013;Adler et al 2014;Huang et al 2015;Perez et al 2015), and only a few strains have been reported as being resistant to this class of antibiotics (Figueira et al 2011;Castelo-Branco Dde et al 2015). The strain of A. dhakensis in the present study was not, however, fully resistant to carbapenems, as susceptibility to imipenem was observed.…”
Section: Discussionmentioning
confidence: 42%
“…; Castelo‐Branco Dde et al . ). The strain of A. dhakensis in the present study was not, however, fully resistant to carbapenems, as susceptibility to imipenem was observed.…”
Section: Discussionmentioning
confidence: 97%